THE INFLUENCE OF LEARNING MOTIVATION, PARENTS SOCIO-ECONOMIC STATUS, AND PEER ENVIRONMENT ON INTEREST IN CONTINUE EDUCATION TO HIGHER EDUCATION - Yohana, Corry; Adha, Maulana Amirul; Sandyaningrum, Meileni (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2023)
This research was conducted to determine the effect of learning motivation, socioeconomic status of parents, and peer environment on the interest in continuing education to higher education in class XII students at SMK N 14 Jakarta. The research method used is a quantitative research method with a descriptive approach. The population used in this study were all students of class XII SMK N 14 Jakarta consisting of 309 students. The number of samples selected using the proportional random sampling technique was 174 students. The research model uses a path analysis model and the data analysis technique used is SEM (Structural Equation Modeling) using the SmartPLS version 4 application. From the results of this study it is known that learning motivation and Peer environment has a positive and significant effect on the interest in continuing education to tertiary institutions. Socioeconomic status of parents has no effect on interest in continuing education to tertiary education. And all of independent variables, have an influence on the interest in continuing education to tertiary institutions.